Guideline-based and bioinformatic reassessment of lesion-associated gene and variant pathogenicity in focal human epilepsies - Niestroj, Lisa-Marie; Du, Juanjiangmeng; Nothnagel, Michael; May, Patrick; Palotie, Aarno; Daly, Mark J.; Nuernberg, Peter; Blümcke, Ingmar; Lal, Dennis (Epilepsia, 2018)
OBJECTIVE: Increasing availability of surgically resected brain tissue from patients with focal epilepsy and focal cortical dysplasia or low-grade glioneuronal tumors has fostered large-scale genetic examination. However, assessment of pathogenicity of germ line and somatic variants remains difficult. Here, we present a state-of-the-art evaluation of reported genes and variants associated with epileptic brain lesions. METHODS: We critically reevaluated the pathogenicity for all neuropathology-associated variants reported to date in the PubMed and ClinVar databases, including 101 neuropathology-associated missense variants encompassing 11 disease-related genes. We assessed gene variant tolerance and classified all identified missense variants according to guidelines from the American College of Medical Genetics and Genomics (ACMG). We further extended the bioinformatic variant prediction by introducing a novel gene-specific deleteriousness ranking for prediction scores. RESULTS: Application of ACMG guidelines and in silico gene variant tolerance analysis classified only seven of 11 genes to be likely disease-associated according to the reported disease mechanism, whereas 61 (60.4%) of 101 variants of those genes were classified as of uncertain significance, 37 (36.6%) as being likely pathogenic, and 3 (3%) as being pathogenic. SIGNIFICANCE: We concluded that the majority of neuropathology-associated variants reported to date do not have enough evidence to be classified as pathogenic. Interpretation of lesion-associated variants remains challenging, and application of current ACMG guidelines is recommended for interpretation and prediction.
EVALuna2:36559